Synthesis and Optical Enhancement of Amorphous Carbon Nanotubes/Silver Nanohybrids via Chemical Route at Low Temperature - Tan Kim Han; Leo Bey Fen; Ng Meng Nee; Mohd Rafie Johan (The Scientific World Journal)
We report the synthesis of amorphous carbon nanotubes/silver (αCNTs/Ag) nanohybrids via simple chemical route without additional reactant and surfactant at low temperature. Field emission scanning microscope (FESEM) and transmission electron microscope (TEM) confirmed formation of CNTs. X-ray diffraction (XRD) pattern confirmed the amorphous phase of carbon and the formation of Ag nanoparticles crystalline phase. Raman spectra revealed the amorphous nature of αCNTs. UV-visible spectroscopy showed enhancement of optical properties of αCNTs/Ag nanohybrids.